2017
DOI: 10.1364/optica.4.001289
|View full text |Cite
|
Sign up to set email alerts
|

Temporal recompression through a scattering medium via a broadband transmission matrix

Abstract: The transmission matrix is a unique tool to control light through a scattering medium. A monochromatic transmission matrix does not allow temporal control of broadband light. Conversely, measuring multiple transmission matrices with spectral resolution allows fine temporal control when a pulse is temporally broadened upon multiple scattering, but requires very long measurement time. Here, we show that a single linear operator, measured for a broadband pulse with a co-propagating reference, naturally allows for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…5b) and reaches ∆ 3 values of 260 nm, about a factor 3 above the bandwidth obtained in the ps (close to monochromatic) regime. This increase is attributed to the coherent gating effect produced by the measurement of the broadband TM transmission matrix [38], which intrinsically enlarges spectral capabilities as recently demonstrated by time gating [41]. When tuning the 2 distance ( 1 is fixed at 2 mm from the diffuser) ( Fig.…”
Section: Enlarging the 3d Refocus Bandwidth Using Broadband Wavefrontmentioning
confidence: 78%
See 2 more Smart Citations
“…5b) and reaches ∆ 3 values of 260 nm, about a factor 3 above the bandwidth obtained in the ps (close to monochromatic) regime. This increase is attributed to the coherent gating effect produced by the measurement of the broadband TM transmission matrix [38], which intrinsically enlarges spectral capabilities as recently demonstrated by time gating [41]. When tuning the 2 distance ( 1 is fixed at 2 mm from the diffuser) ( Fig.…”
Section: Enlarging the 3d Refocus Bandwidth Using Broadband Wavefrontmentioning
confidence: 78%
“…The measured 'broadband TM' has to be distinguished from the 'multispectral TM' reconstructed from a collection of individual monochromatic TM's. The broadband TM has been shown in particular to preserve the short pulse nature of the refocus, due to an intrinsic coherent time gating effect produced by self-reference interferometry [38], provided that the medium bandwidth is comparable with the laser bandwidth. As a consequence a broadband refocus exploits favourably short propagation paths in a scattering medium [40] [38].…”
Section: Enlarging the 3d Refocus Bandwidth Using Broadband Wavefrontmentioning
confidence: 99%
See 1 more Smart Citation
“…External references deliver flat wavefronts, but suffer from instability and make the setup more complex and less compact. The use of an internal reference circumvents this and furthermore benefits from an inherent coherence gating that preserves short pulses [6]. However, there are two drawbacks when using an internal reference encoded onto a spatial light modulator (SLM).…”
Section: Introductionmentioning
confidence: 99%
“…One last perspective could be to extend this study to the broadband regime. Mounaix et al demonstrated a selection of short scattering sequences by exploiting the short coherence length of a pulsed laser through a homogeneous scattering media [24]. By exploiting this effect, one could obtain a further increase in the stability of the focus.…”
Section: Discussionmentioning
confidence: 99%